Management of nipple pain or trauma in breastfeeding mothers in a hospital setting: a best practice implementation project. Issue 3 (19th September 2021) - Yang, Lixia; Wang, Xiaoyang; Luo, Yin; Sun, Fengjiao; Wu, Minyan; Huang, Yacui; Zhang, Qian; Liu, Yawei; Xiao, Lin; Wang, Ning
ABSTRACT: Introduction and aims: Breastfeeding is one of the best ways to ensure healthy growth and development of an infant. Nipple pain and trauma are common complications associated with breastfeeding, which render it difficult for the mother to continue breastfeeding. The aim of this project was to promote evidence-based practice in the management of nipple pain or trauma for breastfeeding mothers in a large tertiary hospital in China. Methods: The project was conducted using the Joanna Briggs Institute framework and Practical Application of Clinical Evidence System. Six audit criteria were applied in baseline and follow-up audits to assess compliance in practice with best practice recommendations. The Getting Research into Practice tool was used to help analyze barriers to the fulfillment of each audit criterion based on the baseline audit results. Implementation strategies were discussed and then undertaken to overcome the barriers and bring changes to the current practice. Results: The baseline audit results demonstrated poor compliance in nipple pain or trauma management practice with all of the six criteria. Significant improvements were achieved in the follow-up audit. Specifically, the compliance rate increased from 15 to 100% for criterion 1 and from 2 to 93% for criterion 2. For criteria 3, 4, 5 and 6, the compliance rate increased from 0 to 90, 85, 100 and 86%, respectively. Conclusion: The current evidence-based implementation project was successfully conducted and achieved great improvement in the management of nipple pain or trauma associated with breastfeeding. Continuous effort is required to maintain changes and further improve practice.